Effects of Glyphosate-Based Herbicide Sub-Lethal Concentrations on Fish Feeding Behavior - Giaquinto, Percilia Cardoso [UNESP]; de Sï¿½, Marina Borges [UNESP]; Sugihara, Vanessa Seiko [UNESP]; Gonï¿½alves, Bruno Bastos [UNESP]; Delï¿½cio, Helton Carlos [UNESP]; Barki, Assaf (Springer Nature, 2017)
Glyphosate-based herbicides are widely used in agricultural systems. Although the target organism are particularly plant organisms, there are numerous studies showing adverse effects in aquatic animals, such as inhibition of acetyl cholinesterase, effects on kidney, liver, and gill and stressors effects. This study analyzed the effects of commercial formulation of glyphosate on feeding behavior in Pacu (Piaractus mesopotamicus). Fish were exposed to three glyphosate concentrations (0.2, 0.6, and 1.8 ppm) for 15 days. At concentrations of 0.2 and 0.6 ppm, food intake decreased on day 13 and then returned to normal on day 15. At the highest glyphosate-based herbicide concentration, 1.8 ppm, food consumption decreased dramatically and did not recover on day 15. This study showed that glyphosate-based herbicide at sub-lethal concentrations can affect feed intake in pacu and consequently inhibits its growth.
Keywords: Feeding behavior; Herbicide; Piaractus mesopotamicus; Roundup